Socioeconomic Analysis Of Tarakan Island Coastal Communities - Sulistya Rini Pratiwi (Publikasi Indonesia, 2023)
The purpose of this study was to determine description of socioeconomic conditions and the magnitude of the value of coastal community willingness to pay in the efforts to overcome the impact of coastal abrasion in Tarakan City. The qualitative descriptive analysis method with the Miles & Huberman analysis design was used to determine the social conditions of coastal community. The method used in calculating the willingness to pay public services was the Contingent Valuation Method (CVM). The results of the analysis obtained that the education level of the coastal community belonged to the medium category, with low income levels. The amount of willingness to pay the public services for the efforts to repair the coastal damage is in average of Idr 83,077. Based on the value of the scenarios offered, this value indicates the high participation of the coastal community in the efforts of repairing damage.